Integrated Local Wisdom Through Minangkabau Culture Education on the Formation of Student Character - Desi Harlina; Firman Firman; Mohd. Suhadi bin Mohammed Sidik (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2024)
This article explains the integration of local policy through Minangkabau cultural education which is carried out for the formation of student characteristics. The decline in the values of nationalism and patriotism as well as the preaching of foreign cultural values, aliveness causes local and national values to be true. So that the need for the formation of student characteristics so that the Minangkabau culture can be practiced by good delay through classrooms at school. The method in writing this article uses the literature study method. The purpose of this study is to shape the character of students through the values of local wisdom Minangkabau has a comprehensive character dimension related to the development of the quality of human resources.